Hypothyroidism Due to Thyroid Amyloidosis Simultaneously With AL Renal Amyloidosis to Give Better Idea of Association of the Two Conditions - Guan C; Liu Y; Chen R; Zhu Y (International Medical Case Reports Journal)
Changrong Guan,1 Yonghua Liu,2 Riqiu Chen,1 Yingbiao Zhu3 1Department of Endocrinology, The Lishui Hospital of Wenzhou Medical University, The First Affiliated Hospital of Lishui University, Lishui People’s Hospital, Lishui, Zhejiang, 323000, People’s Republic of China; 2Department of Hematology, The Lishui Hospital of Wenzhou Medical University, The First Affiliated Hospital of Lishui University, Lishui People’s Hospital, Lishui, Zhejiang, 323000, People’s Republic of China; 3Department of Neurology, The Lishui Hospital of Wenzhou Medical University, The First Affiliated Hospital of Lishui University, Lishui People’s Hospital, Lishui, Zhejiang, 323000, People’s Republic of ChinaCorrespondence: Yingbiao Zhu, Department of Neurology, The Lishui Hospital of Wenzhou Medical University, The First Affiliated Hospital of Lishui University, Lishui People’s Hospital, Lishui, Zhejiang, 323000, People’s Republic of China, Tel +86-18957097750, Email zybiao5107@163.comAbstract: Primary amyloidosis (AL type) is a systemic disease that can lead to structural and functional damage to organs and tissues such as the kidney, heart and liver with non-specific symptoms. Most of the affected patients develop thyroid infiltration and thus diffuse enlargement of the thyroid gland, while cases leading to hypothyroidism are exceedingly rare. Some researchers have analyzed thyroid function in newly diagnosed patients with AL amyloidosis, and found that the incidence of overt hypothyroidism is only 7%. In this case, we describe a 66-year-old female patient who visited the nephrology department due to lower limb edema for 2 months and numbness of the extremities for more than 2 years. Examination revealed massive proteinuria and hypoproteinemia, and a needle biopsy of the kidney revealed amyloid deposition. The patient was also found to have hypothyroidism and diffuse enlargement of the thyroid gland. We evaluated the etiology of thyroid disease from the pathogenesis of the disease after consulting an endocrinologist. The result of the thyroid fine needle puncture and pathological examination showed thyroid amyloidosis. The patient received levothyroxine sodium tablets as replacement therapy and received chemotherapy in the hematology department. At the same time, we monitored the improvement in thyroid function and reduction in thyroid volume.Keywords: thyroid amyloidosis, hypothyroidism, renal amyloidosis, nephrotic syndrome, macroalbuminuria